2022
DOI: 10.1177/23259671221120212
|View full text |Cite
|
Sign up to set email alerts
|

Failure Rates of Suture Anchor Fixation Versus Transosseous Tunnel Technique for Patellar Tendon Repair: A Systematic Review and Meta-analysis of Biomechanical Studies

Abstract: Background: Transosseous tunnel (TO) repair is considered the gold standard for patellar tendon rupture; however, suture anchor (SA) repair has emerged as a viable alternative in recent years. Although both these techniques are used widely in clinical practice, the most biomechanically optimal construct for patellar tendon repair remains unknown. Purpose: To examine published studies on the biomechanical properties of TO and SA fixation for patellar tendon repair in terms of ultimate load to failure and cyclic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
1
2
0
1
Order By: Relevance
“…Imbergamo et al performed a systematic review using PRISMA guidelines, searching PubMed, the Cochrane Library, and Embase to identify studies that analyzed the biomechanical properties of SA and TO techniques for repair of a ruptured patellar tendon, resulting that the use of SA fixation results in decreased cyclic gap formation when compared with TO repair, with no significant difference in ultimate load to failure between the groups. These findings may have meaningful clinical implications, coinciding with existing clinical data demonstrating a decreased failure rate for SA repair in comparison with TO repair for patellar tendon rupture [ 11 ]. Both patellar and quadriceps tendon ruptures are significant cause of morbidity and can have negative short- and long-term effects on patient lives [ 12 ].…”
Section: Discussionsupporting
confidence: 79%
“…Imbergamo et al performed a systematic review using PRISMA guidelines, searching PubMed, the Cochrane Library, and Embase to identify studies that analyzed the biomechanical properties of SA and TO techniques for repair of a ruptured patellar tendon, resulting that the use of SA fixation results in decreased cyclic gap formation when compared with TO repair, with no significant difference in ultimate load to failure between the groups. These findings may have meaningful clinical implications, coinciding with existing clinical data demonstrating a decreased failure rate for SA repair in comparison with TO repair for patellar tendon rupture [ 11 ]. Both patellar and quadriceps tendon ruptures are significant cause of morbidity and can have negative short- and long-term effects on patient lives [ 12 ].…”
Section: Discussionsupporting
confidence: 79%
“…These findings were further corroborated by Lanzi et al 54 in a study on 24 porcine specimens that found markedly less gap formation and higher load to failure with suture anchor versus transosseous tunnels. In a systematic review and meta-analysis of seven studies and a total of 128 cadaveric knees, Imbergamo et al 32 found markedly less gap formation in the suture anchor cohort but did not reveal any notable difference in ultimate load to failure. In a separate meta-analysis, suture anchors again demonstrated favorable biomechanical properties in terms of gap formation when compared with transosseous tunnels.…”
Section: Complete Thickness Rupturementioning
confidence: 98%
“…Although many repair techniques have been reported, repair with transosseous tunnels is the most popular. 31 , 32 This technique typically includes two to four bone tunnels through which sutures are passed and tied (Figures 4 and 5 ). Suture fixation into the tendon is critical for adequate repair, and various suture techniques have been reported.…”
Section: Complete Thickness Rupturementioning
confidence: 99%
“…41 Sin embargo, cada vez hay más evidencia a favor de las anclas sin importar la zona de la lesión. 42 Además, el estudio de O'Dowd y asociados demostró que la reparación con anclas presenta disminución significativa en la tasa de rerrotura, en comparación con la reparación de túneles transóseos. 43 Los cerclajes metálicos protegen la reparación primaria y aumentan la estabilidad de la construcción, disminuyendo la separación en el sitio de reparación y pueden permitir un rango de movimiento más rápido.…”
Section: Autorunclassified